Comparison between Er:YAG laser and bipolar radiofrequency combined with infrared diode laser for the treatment of acne scars: Differential expression of fibrogenetic biomolecules may be associated with differences in efficacy between ablative and non‐ablative laser treatment. Issue 4 (2nd November 2016) - Min, Seonguk; Park, Seon Yong; Moon, Jungyoon; Kwon, Hyuck Hoon; Yoon, Ji Young; Suh, Dae Hun
Abstract : Background and Objective: Fractional Er:YAG minimizes the risk associated with skin ablation. Infrared diode laser and radiofrequency have suggested comparable improvements in acne scar. We compared the clinical efficacy of Er:YAG laser and bipolar radiofrequency combined with diode laser (BRDL) for the treatment of acne scars. Moreover, acute molecular changes of cytokine profile associated with wound healing have been evaluated to suggest mechanisms of improvement of acne scar. Study Design: Twenty‐four subjects with mild‐to‐moderate acne scars were treated in a split‐face manner with Er:YAG and BRDL, with two treatment sessions, 4 weeks apart. Objective and subjective assessments were done at baseline, 1, 3, 7 days after each treatment and 4 weeks after last treatment. Skin biopsy specimens were obtained at baseline, 1, 3, 7, 28 days after one session of treatment for investigation of molecular profile of acute skin changes by laser treatment. Results: Investigator's Global Assessment representing the improvement degree shows 2.1 (50%) in fractional Er:YAG and 1.2 (25%) in BRDL. Er:YAG induced the later and higher peak expression of TGFβs and collagenases, whereas BRDL induced earlier and lower expression of TGFβ and collagenases, relatively. PPARγ dropped rapidly after a peak in Er:YAG‐treated side, which is associated with tissue inhibitor of metalloproteinase (TIMP) expression. We observed higher expression of TIMP after Er:YAG treatment compared with BRDL by immunohistochemistry, which may be associated with the expression of upregulation of collagen fibers. Conclusion: The superior efficacy of Er:YAG to BRDL in the treatment of acne scars may be associated with higher expression of collagen which is associated with differential expression of TGFβs, collagenases, PPARγ, and TIMP. Lasers Surg. Med. 49:341–347, 2017. © 2016 Wiley Periodicals, Inc.